Loss of both wobbleU34 modifications in mcm5s2U tRNAs impairs rRNA biosynthesis, growth, and development in Arabidopsis thaliana - Nakai, Yumi; Kurihara, Yukio; Makita, Yuko; Horiguchi, Gorou; Iwabuchi, Kosei; Harada, Akiko; Nakai, Masato; Yano, Takato (Frontiers in Plant Science, 2025)
In eukaryotic cells, the first anticodon uridine base of cytosolic tRNALys(UUU), tRNAGlu(UUC), and tRNAGln(UUG) (wobbleU34) is post transcriptionally modified through adding a methoxycarbonylmethyl group and substituting a sulfur at the fifth and second carbons, respectively, to form 5-methoxycarbonylmethyl-2-thiouridine. The simultaneous deletion of these two wobbleU34 modifications causes lethality in mice and flies. Here, we report that deletion of both wobbleU34 modifications results in severe growth retardation and morphological abnormalities in Arabidopsis thaliana. The results of Ribo-seq and RNA-seq analyses indicate that the ribosome occupancy of many transcripts is substantially different in the Arabidopsis mutant lacking both wobbleU34 modifications compared with the wild type. Gene Ontology analysis shows that genes with altered ribosome occupancy are categorized as having RNA-binding properties. Several pre-rRNA processing precursors accumulate in the mutant lacking both wobbleU34 modifications. In the mutant, ribosomes likely pause when the cognate [A/G/C]AA codons of tRNALys(UUU), tRNAGlu(UUC), and tRNAGln(UUG) are positioned at the A site during translation of transcripts encoding proteins involved in pre-rRNA processing, such as DRH1 and ATRH7. These findings suggest that deleting both wobble U34 modifications impairs rRNA maturation, leading to the accumulation of rRNA precursors adversely affecting growth and morphogenesis in plants.